The UNEP governance and its challenge towards mechanism of NGO engagement in Indonesia - Paramitha, Gracia; Djati, Sundring (Technium Social Sciences Journal, 2023)
Since the globalization era and the end of the Cold War, the environment is the third agenda after international security and the global economy (Porter and Brown, 1996). In 1972, the Stockholm Conference, the first global environmental meeting, led to the establishment of the United Nations of Environment Programme (UNEP) in 1974. Its aim was for managing global environmental issues under the mandate of the United Nations. Since 1992, there has been a framework to engage civil societies in the UN system and environmental governance, which is called Major Groups. They are children and youth, women, trade unions, farmers, indigenous communities, scientists, business sectors, and NGOs. This Major Groups regularly hold an annual meeting along with UNEP Governing Council Meeting. However, their representatives have not fully participated in the decision-making process. The main reasons were complicated accreditation for Major Groups, lack of access, lack of financial support, and lack of coordination in terms of doing public consultation with the UNEP Governing Council. In the case of Indonesia, no NGO has been included in UNEP-accredited NGOs (UNEP Document, 2013). The research question is why UNEP governance does not fully influence the NGOs in Indonesia. This paper aims to analyze the factors of the weak UNEP governance using a theoretical framework for civic engagement. In its theory, there are 3 key indicators: information, participation, and consultation. This paper used a qualitative method by collecting data and conducting in-depth interviews with WWF Indonesia, WALHI (Indonesian Environmental Forum), and Indonesia Berkebun (Gardening Indonesia). The key finding of the research is that UNEP has weak capability in doing public consultation and national outreach. Hence, UNEP should create National Committee, which strengthens the link between Indonesian NGOs and ASEAN.